MODELSISTEM PENDUKUNG BIMBINGAN SKRIPSI BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI BAGI MAHASISWA JURUSAN PENDIDIKAN AGAMA ISLAM - Khairawati . (AT-TURATS, 2018)
This research aims to examine the application of guidance using thesis supported guidance system based on technology of information and communication for students of Islamic Education Department. Furhermore, the research is written by research and development (R&D) approach. This developed model is a combination of social networking application, e-learning application, and project management application. Besides, this system operationally could be implied to reduce the resistance on writing and finishing the thesis for PAI Department’s students of IAIN Pontianak.